Pengaruh P2P Lending dan KUR Terhadap Pertumbuhan Ekonomi di Seluruh Provinsi Indonesia - Simanjuntak, Cathy Stevani; Andrian, Thomas (CV. ITTC INDONESIA, 2025)
This study aims to analyze the effect of Peer-to-Peer (P2P) Lending and People's Business Credit (KUR) on economic growth in 34 provinces in Indonesia during the period 2018–2023. The data used is panel data that combines time series and cross-sectional dimensions. The analytical method applied is the Generalized Method of Moments (GMM) with a dynamic panel approach to address potential endogeneity and simultaneity bias. The results show that P2P Lending has a negative and significant effect on economic growth, indicating that the increase in P2P Lending activity has not optimally contributed to economic growth, possibly due to high default risks or unproductive fund allocation. On the other hand, KUR has a positive and significant effect on economic growth, reflecting the strategic role of the government financing program in supporting productive sectors. Simultaneously, P2P Lending and KUR together influence economic growth in Indonesia. These findings highlight the importance of strengthening regulations and supervision of P2P Lending, as well as optimizing the distribution of KUR to maximize its impact on the national economy.